The Effect Of Profitability And Company Size On Corporate Sustainability Reporting With Independent Commissioners As A Moderating Variable - Maharani, Septia; Tarmizi, M. Irfan (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the influence of profitability, company size, and independent commissioners on Corporate Sustainability Reporting (CSR) disclosure, as well as to evaluate the role of independent commissioners as a moderating variable. The study was conducted on 27 mining companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024 using a quantitative descriptive and verification approach. Secondary data were analyzed using panel regression with the help of E-Views 12. The results show that profitability and company size have a significant effect on CSR. Independent commissioners do not have a direct effect, but they are able to strengthen the relationship between profitability and CSR, although not on the relationship between company size. These findings indicate that sustainability reporting is more determined by financial performance and business scale, while the oversight function of independent commissioners is still not optimal. Keywords: Profitability; Company Size; Sustainability Reporting; Independent Commissioners.